#TITLE_ALTERNATIVE# - PRIBAWANTO SURYAWAN (NIM 20106006), HERRY
In this thesis we discuss the boundedness of fractional integral operators on non-homogeneous Lebesgue spaces as well as on generalized non-homogeneous Morrey spaces. Non-homogeneous spaces are spaces that are endowed with a growth measure. We will also prove Olsen's inequalities on both spaces.